Avaliação da potencialidade reativa de agregados minerais de Roraima - Lima, Thamires Ohana Coelho (2021)
The Alkali Aggregate Reaction (AAR) is a reaction caused by the high content of alkali present in cement or in the reactive aggregate, in the presence of moisture. It is a deleterious chemical reaction that occurs due to the presence of hydroxide ions (OH-) associated with the alkali content (NaOH) in cement and certain minerals contained in the aggregate. The RAA manifests itself in two ways, namely: Alkali-Silica Reaction (ASR) and Alkali-Carbonate Reaction (ACR). Knowing the geological origin, mineralogical composition and texture of the aggregates is fundamental, it is possible to avoid reactive aggregates in concrete structures, the emergence of this pathological manifestation is prevented. In this context, this work aims to evaluate the reactive potential of rocks used as coarse aggregates from three deposits located in the State of Roraima, Boa Vista and Mucajaí, in the central region, Rorainópolis, located in the southern region. The study started with the physical and chemical characterization of mineral aggregates. After that, the mineralogical phases were identified by means of Xray diffraction (XRD), chemical analysis by energy dispersive X-ray spectrophotometry (EDX) and laser generated plasma spectroscopy (LIBS), reactivity analysis through of petrographic test and expansion test in concrete prisms by the accelerated method. Among three mineral aggregates studied, two were petrographically classified as a granitic rocks with myrmequitic textures, the other one was classified as a basaltic rock. Mineralogically, both showed crystalline phases of plagioclase feldspar. Finally, it was found that the three aggregates are non-reactive, that is, innocuous according to the petrographic analysis and accelerated expansion test in a concrete prism.